Effects of N+-implanted sapphire (0001) substrate on GaN epilayer - Cho, YS; Koh, EK; Park, YJ; Koh, D; Kim, EK; Moon, Y; Leem, SJ; Kim, G; Byun, D (ELSEVIER SCIENCE BV, 2002)
We have investigated the effects of N--implanted sapphire (0 0 0 1) substrate on a GaN epilaver grown by metalorganic chemical vapor deposition (MOCVD). As a result of implantation with 55 keV nitrogenions (N+) to a dose ranging from 1 x 10(5) to 1 X 10(17)cm(-2) prior to GaN epilayer growth. the N+-implanted sapphire surface was chemophysically modified and a thin disordered AIN phase was observed. The N--implanted substrate's surface had decreased internal free energies during the growth of the GaN epilayer, and the misfit strain was relieved through the formation of an AIN phase on the N+ -implanted sapphire (0 0 0 1) substrate. Crystallographical and optical properties of GaN epilayer grown on N+-implanted sapphire (0 0 0 1) substrate with the ion dose of 1 X 10(16)cm(-2) were found to be improved. indicating decreased internal stress and generation of dislocations in the GaN epilayer. The present results show that N--implantation pre-treatment of the sapphire (0 0 0 1) substrate surface can be used to improve the properties of GaN epilayers grown by MOCVD. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: DISLOCATION DENSITY; LATERAL EPITAXY; FILMS; NITRIDE; DEVICES; SURFACE; LAYERS